From the Wrong Point of View! Athletes' Ability to Identify Structured Playing Patterns Suffers from the Misalignment of Tactic Boards during Time-outs in Professional Basketball. (August 2014) - Schul, Karsten; Memmert, Daniel; Weigelt, Matthias; Jansen, Petra
In professional basketball, coaches commonly use time-outs to instruct players on the upcoming playing pattern. In an explorative study a total of 154 time-outs in professional basketball were analyzed and the data revealed that coaches usually present these playing patterns from their own viewing perspective on the tactic board. This habit leads to a misalignment of the instructed playing pattern with the viewing perspective of players, so that they have to mentally rotate the pattern's spatial–temporal information before they can execute the action on the court. In an experimental study thirty-two basketball experts and forty-eight novices watched video clips of different playing patterns, which were presented from their own or from a coaches' viewing perspective. Identification performance suffered significantly for experts and novices when the upcoming pattern was presented upside down. It is suggested that basketball coaches should align their tactic boards with the viewing perspective of their athletes during time-outs.